Potential of Bacteriophages as Non-Alcoholic Antiseptic Hand Sanitizer - Sunarti, Riri Novita; Ike Apriani; Septa Ardiyan Muka Rohma; Adam Ramat hidayat; Frety Abelia Azzumar; Salem Ebraiek (Biota, 2025)
Bacteriophages, or phages, are viruses that can infect and replicate within bacterial cells, such as Escherichia coli. Phages demonstrate a strong ability to lyse host bacteria and exhibit high survivability, making them a promising innovation for use in non-alcoholic antiseptic products, such as hand sanitizer sprays and bacteriophage gels. This study aims to evaluate the effectiveness of bacteriophage-based hand sanitizer sprays and gels in reducing E. coli growth and total microbial colonies on palms, compared to commercial alcohol-based hand sanitizers. The method used in this study is a descriptive quantitative approach using an experimental method, specifically the Hand Sanitizer Spray and Bacteriophage Gel Test as Non-Alcohol Antiseptics. The average total bacterial colonies on male palms for the control treatment, phage gel sanitizer and commercial gel hand sanitizer were 1.95 x 104 CFU/mL; 1.15 x 103 CFU/mL; 2.55 x 103 CFU/mL, respectively,  while on female palms, the values were 2.35 x 104 CFU/mL; 3.05 x 103 CFU/mL; 1.65 x 103 CFU/mL. The average total bacterial colonies on male palms for control treatment, phage sanitizer spray and commercial sanitizer spray were 1.30 x 105 CFU/mL; 2.05 x 103 CFU/mL; 9, 04 x 104 CFU/mL, respectively, while on female palms, the value was 1.58 x 105 CFU/mL; 8.36 x 103 CFU/mL; 8.79 x 104 CFU/mL. The results demonstrated that both bacteriophage hand sanitizer gel and spray significantly reduce bacterial colonies on palms, with phage-based hand sanitizer showing greater efficacy than commercial alcohol-based hand sanitizer.